Reconfigurable embedded Linux project - Karthik Thirugnanam. (2009)
The project is based on a Xilinx University Program Virtex™-II Pro Development System or XUPV2P for short. This system provides an advanced hardware platform that consists of a high performance Virtex-II Pro Platform FPGA surrounded by a comprehensive collection of peripheral components that can be used to create a complex system. A soft-core processor (Generated from software logic) called Microblaze is implemented on this FPGA to act as the CPU of the system. Individual programs can be run as standalone directly on the Microblaze processor, however for more complex functions, having an embedded operating system is advantageous. In this project a distribution called Petalinux is used as the operating system. The purpose of this project is to design a Communication Core, which would enable communication of the processor with off-board circuits, via expansion ports that are provided. This connector would be made to work with the Linux operating system as well. This development would be used to simplify any future projects which would involve the use of this connector to expand the system. Since this project is to be used as a part of future projects, it is important that the method or solution chosen should be easy to re-implement. This implies the ease of implementation in both the hardware domain, and the Linux environment.